Teacher and Students' Opinion on Metacognitive Strategy-Based Instruction Using Song for Listening Skills at High School in Tangerang - Bella Ayu Herawati; Delsa Miranty; Eri Rahmawati (JELLT (Journal of English Language and Language Teaching), 2022)
The purpose of this research is to determine the response of teachers and students to the application of instruction-based metacognitive strategies using English songs for listening lessons. This study uses qualitative methods with research instruments, namely, interviews and was conducted in class 11 Social Sciences at SMAN 10 Tangerang. Four informants, one English teacher, and three grade 11 students were there. Based on the results of the study, it showed that the application of instruction-based metacognitive strategies using songs for listening had a good impact and received positive feedback according to the responses received by the researchers from the results of interviews with one English teacher and three grade 11 students at SMAN 10 Kota Tangerang. In addition, the responses from students, namely students said that the use of songs in listening activities can increase students' enthusiasm for learning, because it makes the listening learning atmosphere fun and not monotonous.